Surveillance of Respiratory Pathogens Among Rapid Diagnostic Test-Negative Acute Respiratory Infection Patients in Myanmar in 2023, with a Focus on Rhinovirus and Enterovirus Genotyping - Yuyang Sun; Tsutomu Tamura; Yadanar Kyaw; Swe Setk; Moe Myat Aye; Htay Htay Tin; Su Mon Kyaw Win; Jiaming Li; Tri Bayu Purnama; Irina Chon; Keita Wagatsuma; Hisami Watanabe; et al. (Viruses)
This study explored the distribution and genetic characteristics of respiratory pathogens in outpatients with acute respiratory infections (ARIs) in Yangon, Myanmar, during the 2023 rainy season. Among 267 patients who tested negative for influenza, RSV, and SARS-CoV-2 using rapid diagnostic tests, 84.6% were positive for at least one pathogen according to a multiplex polymerase chain reaction (PCR) assay, the BioFire® FilmArray® Respiratory Panel 2.1. The most common viruses detected were rhinovirus/enterovirus (RV/EV) at 37.8%, respiratory syncytial virus (RSV) at 22.4%, and human metapneumovirus (hMPV) at 10.0%. These pathogens co-circulated mainly from July to September, with RV/EV consistently predominant. Symptom comparison among RV/EV-, RSV-, and hMPV-infected patients showed similar clinical features, though fever was more common in hMPV cases. Among RV/EV-positive patients, 59.3% had single infections, while 40.7% experienced co-infections, especially with RSV and adenovirus. Genotyping identified 28 types from five species, primarily RV-A and RV-C, which were genetically diverse. One EV-D68 case was also found, emphasizing its potential risk. This study underscores the genetic diversity and clinical impact of RV/EV and stresses the importance of ongoing molecular surveillance in Myanmar’s post-COVID-19 context to inform effective public health responses.